Toward An Effective Supervision of Partially Dollarized Banking Systems - Garcia Pascual, Antonio (IMF Working Papers; Working Paper ;, 2006)
The paper presents a supervisory framework that addresses the vulnerabilities of partially dollarized banking systems. The tendency to underprice systemic liquidity risk and currency-induced credit risk creates vulnerabilities that need supervisory responses. The framework seeks to induce agents to better internalize risks by implementing a risk based approach to supervision, following the risk management guidelines of the Basel Committee, and by establishing buffers to cover higher liquidity and solvency risks. The paper also shows that most dollarized countries have addressed their liquidity vulnerabilities, but few have addressed those arising from currency-induced credit risks.